A 48-year adult male with convulsion, collapses and generalized weakness – a rare presentation of Gitelman’s Syndrome (Community Based Medical Journal, 2022)
Hypokalaemia is a common clinical condition, very often the cause of which can be determined by the patient’s clinical history. Gitelman’s syndrome is an inherited renal tubular disorder that must be considered in some cases of hypokalaemia. We present this case of a 48-year-old male patient admitted in our nephrology department for recurrent hypokalaemia. The patient had generalized seizure followed by unconsciousness, generalized weakness, fatigue, palpitation, orthostatic hypotension and polyuria for one month. Patient was on treatment for systemic hypertension with amlodipine and olmesartan. On blood gas analysis, he had a metabolic alkalosis (pH 7.53; pCO2 40 mm Hg; HCO3 34.1mmol/l). Biochemical analysis revealed hyponatremia (105.8mmol/l), hypokalemia (2.07mmol/l), hypochloraemia (74.0mmol/l), hypomagnesaemia (1.10mmol/l) and hypocalcaemia (7.2 mg/dl). Serum creatinine (1.9 mg/dl) and blood urea (6.3mmol/l) were normal. Further investigations revealed hypocalciuria (0.5mmol/l; NR 2.5–7.5) and increased urinary excretion of sodium (210.0 mmol/l; NR 20–110), Potassium (35mmol/l) and chloride (220mmol/l; NR 55–125). Renal ultra-sonogram was normal. A diagnosis of Gitelman’s syndrome was established. We started treatment with sodium chloride, potassium chloride and magnesium sulfate supplementation. Serum potassium was stabilized around 3mmol/l and the patient had significant clinical improvement. The aim of our article is to remind Gitelman’s syndrome in the differential diagnosis of persistent hypokalemia and to highlight the need for further investigations in patients with recurrent hypokalaemic episodes. This rare, inherited, autosomal recessive renal tubulopathy is associated with several genetic mutations in the thiazide-sensitive sodium chloride co-transporter and magnesium channels in the distal convoluted tubule. Patients with Gitelman’s syndrome present during adolescence or adulthood as an inherited autosomal recessive traits with a wide range of clinical presentations from being asymptomatic to predominant muscular symptoms such as fatigue, weakness in association with hypocalciuria, hypomagnesemia with hypermagnesuria and normal prostaglandin production. Clinical suspicion should be raised in those with recurrent hypokalaemic paralysis with metabolic alkalosis associated with hypomagnesaemia. Treatment of Gitelman’s syndrome consists of long-term potassium and magnesium salt supplementation. In general, the long-term prognosis and life expectancy is excellent.CBMJ 2021 January: vol. 10 no. 01 P: 54-58